Applying cheerful disco learning for improving of motivation and learning result of PKn in grade viii c students junior high school 1 Kebumen in second semester 2013/2014 academic years - Makmuroh, Siti (Universitas Negeri Yogyakarta, 2017)
The aim of this classroom action research is to improve students' learning motivation, learning result of PKn on Basic Competence of Describing Indonesian Government System and the Roles of the State Institutions as the Sovereignty Executive and the characters of Grade VIII C Students of Junior High School 1 of Kebumen in Second Semester of Academic Year 2013/2014 by applying CHEERFUL DISCO learning method. The research is a classroom action research conducted in two cycles; each cycle of which includes planning, conducting, observation, and reflection. The result of the research shows that the learning method was able to improve the students' learning motivation in learning activities from 62.37% in pre cycle to 73.74% in the first cycle, then from 78.91% in the second cycle, improved the PKn learning achievement in mastering concept of the ability to describe Indonesian Government System and the Roles of the State Institutions as the Sovereignty Executive, which can be seen that the students' achievement test result is improving in average from 78.18 with 54.55% of mastery learning in pre cycle to 83.23 with 72.73% of mastery learning in the first cycle, then it was improved to 86.59 in average with 81.82% of mastery learning in the second cycle.